Entwicklung eines mobilen Systems zur Erfassung und Erschließung von Ressourceneffizienzpotenzialen beim Rückbau von Infrastruktur und Produkten ("ResourceApp"): Schlussbericht des Forschungsvorhabens - Volk, Rebekka [Hrsg.] (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2017)
In the described research project, a mobile system was developed to acquire and process sensor data from indoor scenes in buildings. Aim of the project was to identify reconstruct the building structure and create a building inventory as well as to identify resource efficiency potentials. Based on the building inventory, the system calculates an optimized deconstruction project plan. The system was successfully tested in the course of the project in residential houses, offices and a hospita.